2011
DOI: 10.1016/j.molbiopara.2010.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of a putative inner arm dynein heavy chain results in flagellar immotility in Trypanosoma brucei

Abstract: The Trypanosoma brucei flagellum controls motility and is crucial for cell polarity and division. Unique features of trypanosome motility suggest that flagellar beat regulation in this organism is unusual and worthy of study. The flagellar axoneme, required for motility, has a structure that is highly conserved among eukaryotes. Of the several dyneins in the axonemal inner arm complex, dynein f is thought to control flagellar waveform shape. A T. brucei gene predicted to encode the dynein f alpha heavy chain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Finally, we investigated whether knockdown of TbCentrin3 or TbIAD5‐1 caused any ultra‐structural defects in the axoneme by transmission electron microscopy, and the results showed that there was no detectable structural defect in the axoneme (Fig. F), consistent with the results obtained from the work performed in the procyclic form (Wei et al , ) and from the knockdown of other inner‐arm dynein proteins by others (Springer et al , ; Zukas et al , ). Altogether, these results demonstrated that the TbCentrin3–TbIAD5‐1 complex is required for cytokinesis initiation in bloodstream trypanosomes.…”
Section: Resultssupporting
confidence: 85%
“…Finally, we investigated whether knockdown of TbCentrin3 or TbIAD5‐1 caused any ultra‐structural defects in the axoneme by transmission electron microscopy, and the results showed that there was no detectable structural defect in the axoneme (Fig. F), consistent with the results obtained from the work performed in the procyclic form (Wei et al , ) and from the knockdown of other inner‐arm dynein proteins by others (Springer et al , ; Zukas et al , ). Altogether, these results demonstrated that the TbCentrin3–TbIAD5‐1 complex is required for cytokinesis initiation in bloodstream trypanosomes.…”
Section: Resultssupporting
confidence: 85%
“…1). Similarly, RNAi of another inner-arm dynein, DNAH10, in procyclic trypanosomes also caused severe motility defect, but did not disrupt axoneme structure 15, 16 .…”
Section: Resultsmentioning
confidence: 99%
“…These outputs suggest that loss of the cytoplasmic dynein heavy chain (Tb927.7.3160) does not perturb cell cycle distribution; that a putative DNA helicase (Tb927.11.12600) is required for the completion of S phase; and that knockdown of the axonemal dynein heavy chain (Tb927.11.11220) results in endoreduplication in the absence of cytokinesis. Dyneins are cytoskeletal motor proteins that move along microtubules, to produce a flagellar beat, for example (29).…”
Section: A Genome-wide Conditional Knockdown Screen For Cell Cycle Prmentioning
confidence: 99%